National Economy Growth between the Budget Deficit Problem and the Need for Sources of financing - Belaidi , Mohamed (Finance and Business Economies Review, 2023)
This study aims to analyze the development of the public treasury's ability to create financial sustainability. In circumstances where non-hydrocarbon revenues were growing slowly. Likewise, the continued decline in the average price of a barrel of oil, starting in 2018, which led to a significant decrease in petroleum taxation, and therefore in total revenues. Whereas, due to the strong rise in total expenditures, related to current expenditures and capital expenditures, the budget deficit did not shrink, which resulted in a sharp decline in public saving, which made the government borrow from the banking system, especially after consuming the resources of the Revenue regulation fund (RRF). As public saving during the period 2014-2020 was unable to finance public investment, which resulted in an increased demand for financing sources.